The efficacy of problem-solving treatments after deliberate self-harm: meta-analysis of randomized controlled trials with respect to depression, hopelessness and improvement in problems. - Townsend, E; Hawton, K; Altman, D; Arensman, E; Gunnell, D; Hazell, P; House, A; Van Heeringen, K (2001)
BACKGROUND: Brief problem-solving therapy is regarded as a pragmatic treatment for deliberate self-harm (DSH) patients. A recent meta-analysis of randomized controlled trials (RCTs) evaluating this approach indicated a trend towards reduced repetition of DSH but the pooled odds ratio was not statistically significant. We have now examined other important outcomes using this procedure, namely depression, hopelessness and improvement in problems. METHOD: Six trials in which problem-solving therapy was compared with control treatment were identified from an extensive literature review of RCTs of treatments for DSH patients. Data concerning depression, hopelessness and improvement in problems were extracted. Where relevant statistical data (e.g. standard deviations) were missing these were imputed using various statistical methods. Results were pooled using meta-analytical procedures. RESULTS: At follow-up, patients who were offered problem-solving therapy had significantly greater improvement in scores for depression (standardized mean difference = -0.36; 95% CI -0.61 to -0.11) and hopelessness (weighted mean difference =-3.2; 95% CI -4.0 to -2.41), and significantly more reported improvement in their problems (odds ratio = 2.31; 95% CI 1.29 to 4.13), than patients who were in the control treatment groups. CONCLUSIONS: Problem-solving therapy for DSH patients appears to produce better results than control treatment with regard to improvement in depression, hopelessness and problems. It is desirable that this finding is confirmed in a large trial, which will also allow adequate testing of the impact of this treatment on repetition of DSH.